Model of Assistance in Managing Halal Certificates for MSMEs as A Form of Maximization of the Ministry of Religion's Sound Governance Function - Amrizal, Dedi; Yusriati, Yusriati (LP2M INSURI Ponorogo, 2024)
The implementation of Minister of Religious Affairs Regulation Number 20 of 2021 has required MSMEs (Micro, Small, and Medium Enterprises) in North Sumatra to make products that comply with Islamic law or are halal-certified. This research aims to make the halal assistance process for all MSME actors in North Sumatra take place using an ideal and standard mentoring model so that it does not only rely on work procedures and training experience from BPJPH for LP3H UMSU Halal Center halal companions. The method used in this community service is community-based Research (CBR) using a forum group discussion (FGD) approach in training and mentoring. This method is equipped with a borg and gall approach, which has been refined into five stages. The implementation of FGDs on the application of conceptual models that have produced theoretical models, the stages of applying theoretical models on small and large scales, and finally, product evaluation using the N-Gain test to see whether the resulting product is effective. The results of this study reveal that the mentoring model requires halal assistants to supervise MSME actors when processing halal certificates so that negative verbal excesses can be avoided and successful MSME actors can be monitored for business development and consistency in producing halal products. This research product is effective through the N-Gain test